Postpartum Amenorrhoea among Manipuri Women: A Survival Analysis (Journal of Health, Population and Nutrition, 2012)
Among the three major components of a closed birth interval, waiting time to conception can somehow  be managed with effective contraceptives while gestation is universally constant in its duration; the duration  of postpartum amenorrhoea (PPA) varies in complex nature. The present study aimed to investigate  the proximate factors influencing the duration of PPA. A community-based, cross-sectional study was  conducted in four valley districts of Manipur, India, during 1 August?31 December 2009, to analyze  the differentials and determinants of duration of PPA, applying the survival analysis technique. In total,  1,225 ever-married women were selected through two-stage cluster sampling. The median duration of PPA  was 5.7 months. Among the 11 explanatory variables of interest, only three variablesplace of residence  (p